2022
DOI: 10.31557/apjcp.2022.23.2.399
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Visual Inspection with Acetic Acid (VIA) Screening on Cervical Cancer Mortality and Incidence - A Systematic Review and Meta-Analysis

Abstract: Objectives: Despite being a cheap, easy, and commonly used technique for screening early development of cervical cancer, collective evidence on the effect of visual inspection with acetic acid (VIA) for reducing cervical cancer mortality and incidence are conflicting. We conducted a systematic review and meta-analysis to determine the effectiveness of VIA screening on cervical cancer mortality and incidence. Methods: We searched PubMed, Embase, Cochrane library (Cochrane Database of Systematic Reviews & Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…6 However, a recent systematic review and meta-analysis suggested that the effectiveness of VIA in preventing invasive cervical cancer is inconclusive. 7 VIA is inherently subjective, is less sensitive when the entire squamocolumnar junction is not visible and may be impacted by lack of provider experience, acetic acid of insufficient strength or when examination is performed too soon (or too late) after application. Another limitation is that women who were VIA-positive and had colposcopy that revealed no abnormalities often did not have a biopsy or ECC performed; it is possible that some of these women had CIN 2/3 that was not identified.…”
Section: Strengths/limitationsmentioning
confidence: 99%
“…6 However, a recent systematic review and meta-analysis suggested that the effectiveness of VIA in preventing invasive cervical cancer is inconclusive. 7 VIA is inherently subjective, is less sensitive when the entire squamocolumnar junction is not visible and may be impacted by lack of provider experience, acetic acid of insufficient strength or when examination is performed too soon (or too late) after application. Another limitation is that women who were VIA-positive and had colposcopy that revealed no abnormalities often did not have a biopsy or ECC performed; it is possible that some of these women had CIN 2/3 that was not identified.…”
Section: Strengths/limitationsmentioning
confidence: 99%
“…Regarding secondary prevention, the Pap test remains widely recommended in most countries though the WHO advocates using HPV-DNA testing primarily or combined with cytology as the primary screening tool for CC, subject to the available resources and infrastructure. The research on alternative simple and effective approaches, such as see-and-treat strategies with visual inspection with acetic acid, must continue, particularly in those countries where HPV testing/Pap smears are unaffordable ( 35 ). We must critically analyze the cost-benefit challenge in changing the field of CC screening toward molecular tests ( 36 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Padahal Kanker serviks adalah salah satu jenis kanker yang paling umum di kalangan wanita yang disebabkan terutama oleh Human Papiloma Virus (HPV), infeksi dengan genotipe manusia yang berisiko tinggi kanker serviks invasif; lebih dari 70% dari semuanya kanker serviks disebabkan oleh infeksi dengan HPV-16 dan 18 (Hassan et al, 2018;Nuke et al, 2018;Zhang et al, 2021). Menurut (Lohiya et al, 2022;WHO, 2018). Skrining bertujuan untuk mendeteksi perubahan prakanker, yang jika tidak diobati dapat menyebabkan kanker yang dapat meningkatkan angka morbiditas dan mortalitas, (Lohiya et al, 2022;WHO, 2018) Hasil pemeriksaan IVA positif mengalami penurunan dengan dilakukan deteksi dan pengobatan dini bagi kanker serviks.…”
Section: Pembahasanunclassified
“…Menurut (Lohiya et al, 2022;WHO, 2018). Skrining bertujuan untuk mendeteksi perubahan prakanker, yang jika tidak diobati dapat menyebabkan kanker yang dapat meningkatkan angka morbiditas dan mortalitas, (Lohiya et al, 2022;WHO, 2018) Hasil pemeriksaan IVA positif mengalami penurunan dengan dilakukan deteksi dan pengobatan dini bagi kanker serviks. Pada tahun 2020 dan 2021 tidak melakukan krioterapi karena sarana prasarana belum lengkap khususnya CO2.…”
Section: Pembahasanunclassified